Differentiated Management of Synchronous Communication Tools According to Learning Situations: The Case of Videoconferencing and Chat - Ouariach, Fatima Zahra; Nejjari Amel; Khaldi Mohamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article explores the differentiated pedagogical use of synchronous communication tools specifically videoconferencing and chat in relation to various learning situations. Drawing on a techno-pedagogical framework, it examines how these tools can be effectively managed and integrated across four key phases of the learning process: situation, conceptualization, objectivation, and transfer. Each tool offers specific affordances that align differently with pedagogical intentions. Videoconferencing supports real-time verbal interaction, fosters social presence, and enables immediate co-construction of knowledge. In contrast, chat allows for more reflective engagement, written traceability of exchanges, and more balanced participation among learners. The study highlights how these tools can be complementary rather than interchangeable, depending on the learning objectives and context. Strategic guidelines are proposed to help educators make informed decisions about which tool to use at each phase of the learning process. By aligning tool functionalities with the pedagogical purposes of each learning situation, the article provides a structured approach to improving synchronous communication practices in distance education. This analysis contributes to more effective and intentional use of synchronous tools, enhancing learner engagement and the overall quality of online teaching. Ultimately, the article emphasizes the importance of matching technological affordances with instructional design for meaningful learning experiences.